Evaluation of an inkless method for fingerprint recordings using hand sanitizer gel on thermal paper (Part II): Effect of time, temperature, and biological sex. (November 2022) - De Alcaraz-Fossoul, Josep; Li, Sihai
Abstract: This article further investigates the suitability of an inkless method to obtain and maintain exemplar fingerprint recordings on thermal paper; in this case, stored for 1.5 years at different temperatures. Inkless impressions were (re-)examined by optical means via two independent methods. First, an automated metric from the FBI's Universal Latent Workstation (ULW) was adapted (i.e., BlueGreen color-coded maps) to evaluate visual differences among inkless fingerprint sets with respect to storage time, temperature, relative humidity, and biological sex. Additionally, a conventional assessment system was applied, a categorical quality score (QS) metric that ranges on a grading scale from 1 to 4. Results revealed that storage time (72 weeks), as well as a colder temperature (~ 3 ºC) and lower relative humidity (~ 12 %), had little impact on the preservation of ridge clarity when compared to freshly deposited counterparts. A biological sex effect was again detected, but its influence was not significant under certain conditions. Despite minor visual differences, the ridge clarity of the inkless impressions remained stable for the duration of the experiment. The stability and durability of the proposed inkless method were proven, becoming a potential alternative to the conventional black ink method. Highlights: An inkless method for exemplars was tested as a function of time, temperature, and sex. Two metrics, QS and BG, assessed the resulting fingerprint clarity. Time and colder temparatures did not significantly affect fingerprint clarity. The proposed method was proven a stable alternative to the conventional black ink